Application of neighborhood sequences in communication of hexagonal networks - Nagy, Benedek (Elsevier Science Bv, 2017)
In this paper communication in hexagonal network is analyzed. Every vertex of the network has direct connections to its neighbors. They communicate with neighborhood sequences varying the used neighborhood relations in each step. Theoretical results, such as algorithm to provide a shortest path and properties of B-distances are shown. Applications for broadcasting information and for two-way communications are presented and discussed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Neighborhood sequences; Hexagonal network; Digital distances; Digital discs; Communication; Various signal speed